Extracellular Vesicles as Shuttles of Tumor Biomarkers and Anti-Tumor Drugs - Zocco, Davide; Ferruzzi, Pietro; Cappello, Francesco; Kuo, Winston Patrick; Fais, Stefano (Frontiers in Oncology, 2014)
Extracellular vesicles (EV) include vesicles released by either normal or tumor cells. EV may exceed the nanometric scale (microvesicles), or to be within the nanoscale, also called exosomes. It appears mandatory that only exosomes have the size that may be considered suitable for a potential use in nanomedicine, in either diagnosis or therapy. This is of particular interest for research in cancer, also because the vast majority of existing data on EV are coming from pre-clinical and clinical oncology. We know that the microenvironmental features of cancer may favour cell-to-cell paracrine communication through EV, but EV have been purified, characterized and quantified from plasma of tumor patients as well, thus suggesting that EV may have a role in promoting and maintaining cancer dissemination and progression. This is also challenging a promising research on the use of nanovesicles as tumor biomarkers. Moreover, recent research suggests that EV may represent a natural delivery for molecules including drugs and exosomes may represent the ideal natural nanoshuttles for new and old anti-tumor drugs. However, much is yet to be understood about the role of EV in oncology and this article aims to discuss the future of EV in cancer